2018
DOI: 10.1111/jsr.12791
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics, sources of perceived stress and coping strategies in adolescent athletes

Abstract: The aim of the study was to examine sleep characteristics, scheduling of activities, perceived stress and coping strategies between periods of perceived high and low scheduling commitments in adolescent athletes. Twenty adolescents (10 male and 10 female) wore an Actiwatch during two 14‐day testing periods, one in in January (JAN), which was deemed to be a period of low school and sport commitments, and one in March (MAR), during which there was a high volume of school and sport commitments. Actiwatches and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Skein et al. 8 compared two weeks during the holidays to two weeks during school term (inclusive of weekends) and found no significant difference in adolescent athletes sleep duration as assessed by actigraphy. The inclusion of weekend sleep in the Skein et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skein et al. 8 compared two weeks during the holidays to two weeks during school term (inclusive of weekends) and found no significant difference in adolescent athletes sleep duration as assessed by actigraphy. The inclusion of weekend sleep in the Skein et al.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of weekend sleep in the Skein et al. 8 study could have reduced the difference between holiday and school term mean weekly sleep duration. 28 Nonetheless, our findings are in agreeance with previous research in non-athletic adolescent Australian populations, 9 which reported increases in sleep duration of 36 min to 1 h 17 min in the holidays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while the AAP does not recommend the stimulant caffeine to be consumed by adolescents [7], 30-50% report ingesting it [8], which may alter their sleep [9]. Youth athletes face these challenges to their sleep with the additional factors of (a) practice, competition, and travel times that may disrupt sleep [10,11], (b) physical and mental stressors of athletic performance [12], and (c) pain and recuperation due to injury [13].…”
Section: Introductionmentioning
confidence: 99%
“…Athletes can be considered as a vulnerable group of consumers because sport demands an ever-increasing allocation of time and energy [ 11 , 12 ]. Athletes are at the center of the flow of nutrition information [ 13 ], but it is an open-ended question as to how they can process these pieces of knowledge.…”
Section: Introductionmentioning
confidence: 99%